Hubungan Tingkat Pengetahuan Ibu tentang Kontrasepsi dengan Metode Pemilihan Kontrasepsi Hormonal dan Non Hormonal di Desa Ngalian Kabupaten Wonosobo - Oktaviani, Paramita Dian, dr. Iskandar, M.Kes, dr. Burhanudin Ichsan, M.Med.ed (2016)
Background: The family planning program as one of the programs to control the population through birth arrangement. Contraceptive ideal is contraceptive efficiently, safe, cheap, esthetic, can afford, does not require motivation continuously, and minimum side effects. Several factors that to be considered including status of health, side effects, the consequences of failure or an unwanted pregnancy. Objectives: The main objective is to analyze relationship between the level of mother's knowledge about contraception with optionalcontraseptive method's hormonal and non hormonal. Methods: Observational research analytic with the approach cross sectional by means of research of variable dependent and independent in one time. This research will analyze the relationship between mother's knowledge about contraception with optional contraseptive method's hormonal and non hormonal in Ngalian village Wonosobo. The technique sampling uses simple random sampling. Results: Analysis chi-square value p = 0,037 ( p < 0,050 ) can then be concluded that there are relationship between the level of mother's knowledge about contraception with the optional contraseptive method's hormonal and non hormonal. Conclusion: There are relationship between the level of mother's knowledge about contraception with optional contraseptive method's hormonal and non hormonal in Ngalian village Wonosobo.